Bài 1: Thực hiện phép tính: b) (3x + y) (2x^2 + 3xy – 3y^2) c) (x – 2)(x^3 – 4x^2 + 2x – 5) d) (4y – 1)(1 + 4y + 16y^2)

Question

Bài 1: Thực hiện phép tính:
b) (3x + y) (2x^2 + 3xy – 3y^2)
c) (x – 2)(x^3 – 4x^2 + 2x – 5)
d) (4y – 1)(1 + 4y + 16y^2)

in progress 0
Melody 4 tuần 2021-07-09T22:41:09+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-07-09T22:42:21+00:00

    Đáp án:

    `b. 6x^3+11x^2y-6xy^2-3y^3`

    `c. x^4-6x^3+10x^2-9x+10`

    `d. 64y^3-1`

    Giải thích các bước giải:

    `b. (3x+y)(2x^2+3xy-3y^2)`

    `= 6x^3+9x^2y-9xy^2+2x^2y+3xy^2-3y^3` 

    `= 6x^3+11x^2y-6xy^2-3y^3`

    `c.  (x-2)(x^3-4x^2+2x-5)`

    `= x^4-4x^3+2x^2-5x-2x^3+8x^2-4x+10`

    `= x^4-6x^3+10x^2-9x+10`

    `d. (4y-1)(1+4y+16y^2)`

    `= 4y+16y^2+64y^3-1-4y-16y^2`

    `= 64y^3-1`

    0
    2021-07-09T22:42:41+00:00

    `\text{b)}`

    `(3x +y)(2x^2+3xy-3y^2)`

    `= (3x . 2x^2) + (3x . 3xy ) + (-3y^2 . 3x) + (y . 2x^2) + (y . 3xy) + (-3y^2 . y )`

    `= 6x^3 + 9x^2y -9xy^2 + 2x^2y + 3xy^2 -3y^3` 

    `= 6x^3 +11x^2y  – 6xy^2-3x^3`

    `\text{c)}`

     `(x-2)(x^3-4x^2+2x-5)`

    `= (x . x^3) + (-4x^2 . x) + (x . 2x) + (5 . x) + (-2 . x^3) + [ (-2) . (-4x^2) ] + (-2 . 2x) + [ (-2)(-5)]`

    `= x^4 -4x^3 + 2x^2 +5x  -2x^3 + 8x^2 -4x +10`

    `= x^4 – 6x^+10x^2 -9x+10`

    `\text{d)}`

    `(4y-1)(1+4y+16y^2)`

    `= 4y + (4y . 4y) + (4y . 16y^2) + (-1 . 1) + (-1 . 4y) + (-1 . 16y^2)`

    `= 4y + 16y^2 + 64y^3 – 1 -4y – 16y^2` 

    `= 64y^3 -1`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )